The influence of music tempo and traffic density on driver performance using galvanic skin response method - Rahmadina, Gayatri Aleyda; Tranggono, Tranggono; Rafi, Rafi (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
The number of traffic accidents in the city of Surabaya during the period 2020 to 2022 tends to increase. Human factors contribute the largest percentage that causes traffic accidents. Some of the causes are impaired driver alertness and stress when driving due to congested road conditions. Listening to music is a distraction while driving because the tempo of the music can affect the driver's cognitive abilities. This research aims to determine the effect of music tempo and traffic density on driver performance. The stress level of the driver's performance will be measured through psychological changes in the skin as a result of changes in sweat gland activity using the galvanic skin response method. The data collection process was carried out experimentally using a driving simulator and a galvanic skin response tool. Data processing was carried out using normality tests, homogeneity tests, and two-way ANOVA tests. The results show that music tempo and traffic density do not have a significant effect on driver stress levels and driver performance. The results obtained in this test were carried out on 10 respondents and the experiment time was quite short, so the results obtained can still change and the experiment must be repeated using the same method to ensure that the results obtained are valid and reliable.